Phylogenetic analysis of the viral proteins VP4/VP7 of circulating human rotavirus strains in China from 2016 to 2019 and comparison of their antigenic epitopes with those of vaccine strains - Mao, Tongyao; Wang, Mengxuan; Wang, Jindong; Ma, Yalin; Liu, Xiafei; Wang, Mingwen; Sun, Xiaoman; Li, Lili; Li, Huiying; Zhang, Qing; Li, Dandi; Duan, Zhaojun (Frontiers in Cellular and Infection Microbiology, 2022)
Group A rotaviruses (RVAs) are the most common etiological agents of severe acute diarrhea among children under 5 years old worldwide. At present, two live-attenuated RVA vaccines, LLR (G10P[15]) and RotaTeq (G1–G4, G6 P[8], P[5]), have been introduced to mainland China. Although RVA vaccines can provide homotypic and partially heterotypic protection against several strains, it is necessary to explore the genetic and antigenic variations between circulating RVAs and vaccine strains. In this study, we sequenced viral protein VP7 and VP4 outer capsid proteins of 50 RVA strains circulating in China from 2016 to 2019. The VP7 and VP4 sequences of almost all strains showed high homology to those of previously reported human strains and vaccine strains of the same genotype. However, in the presumed antigenic epitopes of the VP7 and VP4, multiple amino acid variations were found, regardless of the G and P genotypes of these strains. Moreover, all circulating G3 RVA strains in China potentially possess an extra N-linked glycosylation site compared with the G3 strain of RotaTeq. The potential N-linked glycosylation site at residues 69–71 was found in all G9 strains in China but not in the G9 strain of the Rotavac or Rotasill vaccine. These variations in antigenic sites might result in the selection of strains that escape the RVA neutralizing-antibody pressure imposed by vaccines. Furthermore, the G4 and P[6] genotypes in this study showed high homology to those of porcine strains, indicating the transmission of G4 and P[6] genotypes from pigs to humans in China. More genetic surveillance with antigenic evaluation in prevalent RVAs is necessary for developing and implementing rotavirus vaccines in China.